Riots in Matonge and… the indifference of public authority? - Sarah Demart (Brussels Studies)
Twenty years after the first “North African” riots, in the winter of 2011‑2012 Brussels was the scene of “Congolese” demonstrations which some media and political officials qualified as riots. The idea that political conflicts of the Democratic Republic of the Congo (DRC) had been transposed to Belgium took hold, while the material damage, despite especially heavy riot suppression measures, seemed to have solidly entrenched the image of the violent demonstrator who only understood the language of the nightstick. Based on an ethnographic study of these demonstrations and research in Congolese communities over the past 10 years, the author takes another look at these two weeks of urban violence to ask, on the one hand whether these demonstrations could be actually qualified as riots, and on the other whether the differential treatment by the State compared to the North African riots may be the expression of a significant ethnicization of public policies.